Effectiveness of Problem-Based Learning Assisted by Digital Comic Media on Students’ Critical Thinking - Rachel Brigita Putri Bintan; Rahman, M Fathur (Universitas Negeri Semarang, 2025)
This research aims to evaluate the effectiveness of problem-based learning (PBL) learning models, which use digital comics to develop the students’ ability to think critically. Critical thinking is an important aspect of education that equips students to solve problems and make rational decisions. PBL uses a problem-centered learning approach that is expected to improve this ability, and the use of digital comics is expected to increase students' motivation and critical thinking skills in the learning process. The methods applied in this study are quasi-experimental with a nonequivalent control group design. The research sample consists of 282 students from class XI who chose an interest in economics at SMA Negeri 1 Jogonalan, which is divided in a random way into two groups: an experiment group using PBL with the help of digital comics and a control group that only uses the conventional learning model. The study showed that there was a significant difference in the improvement of critical thinking skills between the experimental group and the control group, with the experimental group showing a higher improvement. This finding indicates that the implementation of PBL assisted by digital comics is effective in encouraging students to analyze, conclude, and understand the connections between ideas, improving students' critical thinking skills. Therefore, this learning model can be considered an innovative alternative for improving the quality of learning and developing students' critical thinking skills in schools.